2016
DOI: 10.1002/2016gl068694
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic near‐term climate variability and the role of a resolved Gulf Stream

Abstract: There is a continually increasing demand for near‐term (i.e., lead times up to a couple of decades) climate information. This demand is partly driven by the need to have robust forecasts and is partly driven by the need to assess how much of the ongoing climate change is due to natural variability and how much is due to anthropogenic increases in greenhouse gases or other external factors. Here we discuss results from a set of state‐of‐the‐art climate model experiments in comparison with observational estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 41 publications
(55 reference statements)
2
69
0
Order By: Relevance
“…Rather, here we have used HiGEM-DP to test the robustness of the mechanisms that lead to skill in decadal predictions of the North Atlantic. Although we can not say anything definitively in terms of the impact of resolution on prediction skill, evidence does support an important role for model resolution (atmosphere and ocean) in terms of capturing response of the atmosphere to oceanic anomalies (Minobe et al 2008;Bryan et al 2010;Siqueira and Kirtman 2016). In that regard, improved resolution may have had an impact on the atmospheric response in the early-1990s in HiGEM-DP hindcasts (i.e.…”
Section: Discussionmentioning
confidence: 81%
“…Rather, here we have used HiGEM-DP to test the robustness of the mechanisms that lead to skill in decadal predictions of the North Atlantic. Although we can not say anything definitively in terms of the impact of resolution on prediction skill, evidence does support an important role for model resolution (atmosphere and ocean) in terms of capturing response of the atmosphere to oceanic anomalies (Minobe et al 2008;Bryan et al 2010;Siqueira and Kirtman 2016). In that regard, improved resolution may have had an impact on the atmospheric response in the early-1990s in HiGEM-DP hindcasts (i.e.…”
Section: Discussionmentioning
confidence: 81%
“…In general, these models improve on many of the shortcomings in coarser resolution, non-eddy resolving climate models, as described in a recent review (Hewitt et al 2017 and references therein). In particular, air-sea interaction in the Gulf Stream is improved in eddy-resolving coupled climate models, and hence, would be necessary to resolve also in dynamical prediction systems (Siqueira and Kirtman 2016). In the region targeted in this study, the eddies role in the mean northward ocean heat transport have shown to be negligible (e.g., Volkov et al 2008;Kirtman et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution coupled climate model and their performance have been explored in several studies during the last decade (e.g., Shaffrey et al 2009;Bryan et al 2010;Delworth et al 2012;Kirtman et al 2012;Marzocchi et al 2015;Siqueira and Kirtman 2016). In general, these models improve on many of the shortcomings in coarser resolution, non-eddy resolving climate models, as described in a recent review (Hewitt et al 2017 and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there are many outstanding questions regarding the nature of underlying mechanisms at high resolution, how much of the knowledge gained through low-resolution studies will carry over, and whether North Atlantic predictability will be sensitive to resolution. To our knowledge, only one study has systematically assessed the change in decadal prediction skill associated with horizontal resolution [130•], and only one so far has looked at decadal predictability with an eddying ocean model [179]; more will undoubtedly follow.…”
Section: Towards Improved Model Fidelitymentioning
confidence: 99%